Dimensi Kosep Wisata Halal: al-Dlaruriyat al-Sitt Pemandian Air Panas Sariater di Subang - Husen, Fathurrohman; Abas, Zainul; Anggrella, Dita Purwinda; Purwono, Purwono (Universitas Islam Negeri Raden Intan Lampung, 2025)
The concept of halal tourism has become a trend and focus of discussion lately. This shows the dynamization of fiqh in the tourism sector. This study aims to explore how the management of Sariater hot springs in Subang responds to fiqh, which is the needs of tourists who implement the concept of halal tourism. The method used is qualitative with primary data from interviews with tourism managers and site observations. Secondary data uses documentation of releases on internet media. As a result, the manager of Sariater responds to the dynamism of fiqh owned by tourists by making policies that lead to the concept of halal tourism. There are three actions that researchers get; first, maintaining cleanliness and preserving trees around tourist attractions, reflecting hifzu al-bi’ah; second, providing special facilities for women (Women Only), demonstrating hifzu al-din; third, monitoring water temperature and mineral content to ensure compliance with hifzu al-nafs. The author recommends that additional facilities be provided in the future, such as halal-certified food and beverages, as well as sharia-compliant massage services, to enhance the overall halal tourism experience and attract more Muslim and non-Muslim tourists